Acute kidney Injury in Children: Impacts and its Management - Quddus, ASM Ruhul; Hasan, Mahmud Javed (Community Based Medical Journal, 2018)
The incidence of acute kidney injury (AKI) in children is increasing globally and is associated with increased mortality and long-term renal consequence.The definition of pediatric AKI was standardized for a more accurate assessment of the epidemiology of pediatric AKI. The definition of AKI is based on elevation in serum creatinine levels or decrease inurine output; accordingly, epidemiological studies have ensued. Recent advances in leveraging electronic medical health record systems and newbiomarkers appear to detect AKI earlier and predict prognosis more accurately than traditional markers have allowed for real-time risk stratification and prevention of pediatric AKI in the hospital setting. For high risk or early stage AKI patients, avoidance of nephrotoxins, optimization of blood pressure and volume status, sufficient nutritional support are necessary and have been demonstrated tobe effective in preventing the occurrence of AKI and improving prognosis. Lastly, renal replacement therapy is needed when conservative care fails. Further therapeutic innovation willdepend on improving the understanding of the basic mechanisms underlying AKI in children. CBMJ 2018 January: Vol. 07 No. 01 P: 48-53